(untitled) (International Journal of Ayurveda and Pharma Research, 2023)
Hairs play an important role in making body externally beautiful, mentally enthusiastic and healthy. Hair loss is common clinical complaint due to pollution, unhealthy diet, physical or emotional stress, poor hygiene and infection. Patchy hair loss considered as Alopecia. Tinea capitis is irregular patchy hair loss due to infection. In Ayurveda hair loss considered as Indralupta. Aim: To study the concept of Ayurvedic treatment in respect to Indralupta. Material and Methods: A Female child age 10 years suffering from multiple patches of hair loss over the scalp. Itching, Redness, Slight local pain during combing scaly patches that may blister and ooze has been reported. It was treated with Ayurvedic medicine both Internal and external for a period of 2 month. Result: After 15 days associated symptoms (itching, redness, inflammation, blister) was reduced. After 1 month the patient was examined for presence of hair follicles and growth of hair over affected area. Conclusion: The given Ayurvedic treatment was successful in treating the Indralupta.